In vitro antifungal and physicochemical properties of polymerized acrylic resin containing strontium-modified phosphate-based glass - Eun-Jee Jang; Ye-Ji Hong; Yoon-Ha Jeong; Kyoung-Eun Kim; Eun-Seo Jo; Myung-Jin Lee; Song-Yi Yang (BMC, 2024)
Abstract Acrylic resins are widely used as the main components in removable orthodontic appliances. However, poor oral hygiene and maintenance of orthodontic appliances provide a suitable environment for the growth of pathogenic microorganisms. In this study, strontium-modified phosphate-based glass (Sr-PBG) was added to orthodontic acrylic resin at 0% (control), 3.75%, 7.5%, and 15% by weight to evaluate the surface and physicochemical properties of the novel material and its in vitro antifungal effect against Candida albicans (C. albicans). Surface microhardness and contact angle did not vary between the control and 3.75% Sr-PBG groups (p > 0.05), and the flexural strength was lower in the experimental groups than in the control group (p < 0.05), but no difference was found with Sr-PBG content (p > 0.05). All experimental groups showed an antifungal effect at 24 and 48 h compared to that in the control group (p < 0.05). This study demonstrated that 3.75% Sr-PBG exhibits antifungal effects against C. albicans along with suitable physicochemical properties, which may help to minimize the risk of adverse effects associated with harmful microbial living on removable orthodontic appliances and promote the use of various materials.